2019
DOI: 10.1002/jbio.201900083
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of long pulse 1064 and 2940 nm lasers in noninvasive lipolysis and skin tightening

Abstract: Noninvasive body shaping is becoming a growing demand. The aim of this study was to investigate the efficacy and safety of the combined treatments of 1064 nm Nd:YAG and 2940 nm Er:YAG in noninvasive lipolysis and skin tightening. Ten females were enrolled, and all women's side of the waist or the lower part of the abdomen were treated. In the first step, the 1064 nm Nd:YAG was used. As a second step, the 2940 nm Er:YAG laser was applied. Each woman was treated four times, once every 2 weeks. The effects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 29 publications
(27 reference statements)
1
8
0
1
Order By: Relevance
“…Improved wrinkle appearance that was evident from the results of our study could be attributed to improved skin elasticity, which has previously been proved to be achieved using the same SMOOTH™ laser modality [35].…”
supporting
confidence: 72%
“…Improved wrinkle appearance that was evident from the results of our study could be attributed to improved skin elasticity, which has previously been proved to be achieved using the same SMOOTH™ laser modality [35].…”
supporting
confidence: 72%
“…A máj vizsgálata tekintetében említésre méltó, hogy az elasztográfia mint vizsgálómódszer szerepel a hepatitis B-és D-vírus-fertőzés diagnosztikájával foglalkozó hazai konszenzusajánlásban, valamint egyik alapvető vizsgálóeljárása a májat érintő klinikai kutatásoknak [7,8]. Szintén hazai közlemények húzzák alá az UHE lehetséges szerepét az emlőrák diagnosztikájában, de bőrgyógyászati és colorectalis alkalmazásáról is olvashatók folyóiratcikkek [9][10][11]. Az UHE egyre növekvő számú közleménnyel alátámasztva mindinkább szerepet kap a szülészeti-nőgyógyászati betegségek és állapotok diagnosztizálásában is.…”
Section: öSszefoglaló Közleményunclassified
“…In some literature reports, PBM is associated with aerobic or resistance exercise, while other reports have mentioned waist and arm circumference reductions with the use of PBM, displaying an absence of diet restrictions or exercise requirements. [25][26][27][28][29] It is also reported that the amount of fat mobilised during a PBM session is similar to the amount that is consumed during a meal, in such a way that it can be absorbed by normal body energy requirements (and/or exercise routine), while at the same time, the risk of atherosclerosis is not increased by the treatment. 30 On the other hand, if not consumed, these fatty acids may be re-esterified and redistributed throughout the body, 30 causing no final changes in waist circumference.…”
Section: Open Accessmentioning
confidence: 99%